(untitled) (Journal of Forest and Livelihood, 2004)
This paper provides a brief overview of the main achievements and challenges of the community forestry approach to improve people’s livelihood and forest condition. The paper demonstrates that Forest User Groups have been able to manage thousands of hectares of community forests, and as a result have contributed to the improvement of forest condition and people’s livelihoods in a number of ways such as capital formation; governance reform, community empowerment and social change. Yet, the livelihoods of the poor and disadvantaged, have not improved as expected. The poorest suffer the most since they cannot afford to participate, are unable to speak out, and are rarely heard when they do. Nevertheless, the community forestry approach is a source of inspiration for the establishment of good forest governance, sustainable forest management and is one of the means to improve people’s livelihoods. To make community forestry pro-poor, further innovation, reflection and improvements are required. The paper suggests a number of pro-poor strategies in order to address the livelihood needs of poor people.